Mohammed Arkoun's Islamology: Applications of Humanities and Social Sciences in Islamic Studies - Pratama, Aunillah Reza; Masruchin, Masruchin (Indonesian Journal of Islamic Theology and Philosophy, 2024)
Abstract;This study focuses on Arkoun's thoughts on the idea of Applied Islamology. Arkoun has anxiety about the treasures of Islamic turats (heritage of tradition, culture, knowledge) which tend to be passive towards advanced civilization in thought. Such stagnation, according to Arkoun, is caused by the hegemony of dogmatic orthodoxy that shackles knowledge into the old episteme. Arkoun's Applied Islamology is a scientific practice in an epistemology of thought. By using the literature method, this study found that the reading of QS. At-Taubah: 5 there is a fairly strong normative foundation about jihad and today's problems regarding it. The results of the reading with several perspectives, namely: from the semiotic side, all vocabulary in Surah At-Taubah is related to the meaning of taubah, including prayer, zakat, faith and disbelief.Keywords:Applied Islamology; Arkoun; Episteme; Socio-Humanities Applications. Abstrak;Kajian ini berfokus pada pemikiran Arkoun tentang gagasan Islamologi Terapan. Arkoun memiliki kegelisahan terhadap khazanah turats Islam (warisan tradisi, kebudayaan, pengetahuan) yang cenderung pasif untuk menuju peradaban maju dalam pemikiran. Kejumudan demikian menurut Arkoun disebabkan oleh hegemoni ortodoksi-dogmatis yang membelenggu pengetahuan ke dalam episteme lama. Islamologi Terapan yang dicetus oleh Arkoun merupakan suatu praktik ilmiah dalam suatu epistemologi pemikiran. Dengan menggunakan metode pustaka, penelitian ini menghasilkan bahwa pembacaan terhadap QS. At-Taubah terdapat landasan normative yang cukup kuat tentang jihad dan problem dewasa ini mengenai hal tersebut. Dalam kasus at-Taubah ini, ayat payung ini adalah ayat saif atau pedang. Ayat pedang yang dimaksud adalah QS. At-Taubah: 5. Hasil pembacaannya dengan beberapa perspektif yaitu: dari sisi semiotik, semua kosa kata dalam surat at-Taubah berkaitan dengan makna taubah, termasuk salat, zakat, iman, kafir.Kata Kunci:   Aplikasi Ilmu Sosial-Humaniora; Arkoun; Episteme; Islamologi Terapan.